2016
DOI: 10.1177/0093854816632551
|View full text |Cite
|
Sign up to set email alerts
|

A Time-Varying Model of Risk for Predicting Recidivism Among Women Offenders Over 3 Years Following Their Release From Jail

Abstract: This study examines time-varying gender-responsive and gender-neutral predictors of recidivism over 3 years using baseline and quarterly follow-up interviews with 477 women released from a county jail. Of the 55 time-varying predictors tested in the longitudinal analysis, 39 were significant predictors of recidivism (new arrest or incarceration) even after controlling for baseline fixed predictors. Stepwise multivariate analysis simplified the model to 12 significant variables, including three time-varying var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 60 publications
1
13
0
Order By: Relevance
“…Along with pathways that mirrored justice-involved men, Daly (1992) identified multiple pathways to offending in justice-involved women, which included victimization and substance abuse. Researchers continue to find support for these “gendered” pathways through studies highlighting the prevalence of victimization and substance abuse in samples of justice-involved women (Brennan, Breitenbach, Dieterich, Salisbury, & Van Voorhis, 2012; Messina, Grella, Burdon, & Prendergast, 2007; Salisbury & Van Voorhis, 2009; Scott et al, 2016). Furthermore, studies have identified the significance of mental health in the criminal pathways of justice-involved women (DeHart, Lynch, Belknap, Dass-Brailsford, & Green, 2014; Salisbury & Van Voorhis, 2009), although this role may be complex.…”
Section: Gender-informed Pathways To Offending and Reoffendingmentioning
confidence: 99%
See 1 more Smart Citation
“…Along with pathways that mirrored justice-involved men, Daly (1992) identified multiple pathways to offending in justice-involved women, which included victimization and substance abuse. Researchers continue to find support for these “gendered” pathways through studies highlighting the prevalence of victimization and substance abuse in samples of justice-involved women (Brennan, Breitenbach, Dieterich, Salisbury, & Van Voorhis, 2012; Messina, Grella, Burdon, & Prendergast, 2007; Salisbury & Van Voorhis, 2009; Scott et al, 2016). Furthermore, studies have identified the significance of mental health in the criminal pathways of justice-involved women (DeHart, Lynch, Belknap, Dass-Brailsford, & Green, 2014; Salisbury & Van Voorhis, 2009), although this role may be complex.…”
Section: Gender-informed Pathways To Offending and Reoffendingmentioning
confidence: 99%
“…This line of inquiry has consistently identified a divergence in criminal pathways between justice-involved women and men (see Vogel & Nicholls, 2016). Relatedly, researchers have identified gender-specific factors that are demonstrative of risk for recidivism in justice-involved women (Salisbury & Van Voorhis, 2009; Scott, Grella, Dennis, & Funk, 2016; Van Voorhis, Wright, Salisbury, & Bauman, 2010). A recent study conducted by Wijkman and Bijleveld (2013) extended support for the importance of gender-specific risk factors for females who have sexually offended, although these findings have yet to be examined further.…”
mentioning
confidence: 99%
“…Kathleen Daly's (1992) Research has consistently found that women offenders report higher incidences of lifetime trauma, emotional problems, and mental health concerns than men prisoners and women in the general population (DeHart, Lynch, Belknap, Dass-Brailsford, & Green, 2014;Drapalski, Youman, Stuewig, & Tangney, 2009;Fazel & Seewald, 2012;Grella, Lovinger, & Warda, 2013). Some studies found victimization is associated with recidivism (Herbst, Branscomb-Burgess, Gelaude, Seth, Parker & Fogel, 2016;Taylor, 2015) and experiencing any trauma within the past year and history of physical abuse as an adult are significant predictors of recidivism (Bonta, Pang & Wallace-Capretta, 1995;Scott, Grella, Dennis & Funk, 2016).…”
Section: Deprivation and Importation Theorymentioning
confidence: 99%
“…The literature provides support for the utilization of gender-informed factors in predicting recidivism. Poverty (Holtfreter, Reisig & Morash, 2004), dysfunctional relationships (Cobbina et al, 2012), exposure to trauma after incarceration (Scott et al, 2016), substance abuse (Taylor, 2008), and mental health issues (Becker, Kerig, Lim & Ezechukwu, 2012) .01 for number of misconducts and any misconducts for 6-month and 12-month incarceration periods), and current psychosis (correlation coefficients ranged from r = .16, p < .01 to r = .31, p < .01 for number of misconducts and any misconducts for 6-month and 12-month incarceration periods). Wright et al (2007) found when gender-neutral and gender-informed needs were separately added to risk (the Institutional Risk Scale), correlations for the Gender-Neutral Needs scale combined with the Institutional Risk Scale were highly significant (correlation coefficients ranged from r = .23 to r = .33, p < .01 for number of misconducts and any misconducts for 6month and 12-month incarceration periods), and correlations for the Gender-Responsive Needs scale combined with the Institutional Risk Scale were also highly significant (correlation coefficients ranged from r = .27 to r = .34, p < .01 for number of misconducts and any misconducts for 6-month and 12-month incarceration periods).…”
Section: Predictors Of Institutional Misconduct For Women Offendersmentioning
confidence: 99%
“…Family relationships and parent–child relationships affect criminal behavior, with strong family relationships precluding future crime. For women, these relationships are particularly important as having a child in foster care or having their parental rights terminated increases their chances of recidivism (Scott et al, 2016). In fact, women who are not parenting their children tend to miss more postsupervision appointments (Stalans & Lurigio, 2015).…”
Section: Literature Reviewmentioning
confidence: 99%